Biocatalytic Synthesis of α,β-Unsaturated 2-Keto Acids and Derivatives Using the Promiscuous Aldolase, NahE - Fansher, Douglas J.; Ngwira, Niza; Salehi, Ahmad Reza; Woods, Jerome; Cascão, Amanda; Palmer, David R. J. (Synthesis, 2022)
Type I aldolases catalyze carbon–carbon bond-forming reactions to form a diverse set of products in nature but often display high selectivity for their natural substrates. One such aldolase, NahE, is known to catalyze the condensation of pyruvate with a wide range of aldehydes to give trans-4-phenyl-2-oxo-3-butenoic acids under mild aqueous conditions. These α,β-unsaturated 2-oxo acids are versatile intermediates for synthetic transformations. NahE has also been used for the synthesis of α-fluoro-β-hydroxy esters, β-hydroxy esters, and quinaldic acids. However, a thorough study of the substrate scope on a practical scale has not been performed for the native NahE-catalyzed aldol condensation reaction. Here we report that NahE can accept >35 (hetero)aromatic and aliphatic aldehydes. Most condensation products derived from substituted benzaldehydes were isolated in >95% yield without need for further purification, while non-benzaldehyde substrates gave the corresponding products in isolated yields between 26% and 98%. Reactions could be performed on gram scale. These products could be converted into α,β-unsaturated carboxylic acids in up to 93% yield over two steps. This reaction sequence was also performed using whole cells in up to 79% yield. This work demonstrates that NahE is a robust, efficient, and versatile catalyst for organic synthesis.
Keywords: aldolase; NahE; biocatalysis; chemoenzymatic synthesis; aldol condensation; cinnamic acids